Investment traps and resilience to shocks: An experimental study of Central Asian collective water governance - Iroda Amirova; Martin Petrick; Nodir Djanibekov (Irrigation and Drainage, 2022)
We theoretically and empirically investigate the investments of water users in a stylized local irrigation system. We model irrigation self-management as an interdependent interaction of users in an evolutionary game and study the resilience of the irrigation system. The theoretical model implies multiple stable equilibria at different efficiency levels. Users may be trapped in a low level of collective investment or succeed by being locked in a high collective investment level, implying an irrigation system resilient against external shocks. The study seeks to empirically identify such lock-ins in experimental interactions among Central Asian farmers. Furthermore, we inquire into whether a pre-play cheap talk opportunity with peer-monitoring or sanctioning treatments influence the self-reinforcing dynamic. Our findings revealed several stable states. Among these states, there are both low and high levels of efficiency, which we measure in the size of public good. Communication among users results in higher collective investment levels. However, this does not guarantee the complete elimination of inferior conventions from best-response play. Penalties crowded out the intrinsic motivation to cooperate as they reduced collective investment in both low- and high-level equilibria. Our findings imply that institutional settings tailored to each community can improve resilience to climate-driven perturbations in water resources. – – Nous étudions théoriquement et empiriquement les investissements des usagers de l'eau dans un système d'irrigation local stylisé. Nous modélisons l'autogestion de l'irrigation comme une interaction interdépendante des usagers dans un jeu évolutif et étudions la résilience du système d'irrigation. Le modèle théorique implique plusieurs équilibres stables à différents niveaux d'efficacité. Les utilisateurs peuvent être piégés dans un faible niveau d'investissement collectif ou réussir en étant enfermés dans un niveau d'investissement collectif élevé, ce qui implique un système d'irrigation résistant aux chocs externes. L'étude cherche à identifier empiriquement ces blocages dans les interactions expérimentales entre les agriculteurs d'Asie centrale. En outre, nous cherchons à savoir si une opportunité de conversation bon marché avant le jeu avec des traitements de surveillance par les pairs ou de sanction influence la dynamique d'auto-renforcement. Nos résultats ont révélé plusieurs états stables. Parmi ces États, il existe à la fois des niveaux d'efficacité faibles et élevés, que nous mesurons par la taille du bien public. La communication entre les utilisateurs se traduit par des niveaux d'investissement collectif plus élevés. Cependant, cela ne garantit pas l'élimination complète des conventions inférieures du meilleur jeu de réponse. Les pénalités ont évincé la motivation intrinsèque à coopérer car elles ont réduit l'investissement collectif dans les équilibres de bas et de haut niveau. Nos résultats impliquent que les cadres institutionnels adaptés à chaque communauté peuvent améliorer la résilience aux perturbations climatiques des ressources en eau.
Keywords: 330; Central Asia; experiment; multiple equilibria; resilience; water management; Asie centrale; expérimentation; équilibres multiples; résilience; gestion de l'eau